Nationality Value Depicted in When English Rings a Bell Textbook: Content Analysis - Ainu Zumrudiana; Aprilia Susanti; Mufidatul Aslamiyah (Language Center of Islamic Institute of Uluwiyah (IAI Uluwiyah) Mojokerto Indonesia, 2022)
In recent years, there has been a growing interest in the integration of moral values into language textbook. This study aims to investigate the value nationality values in When English Rings a Bell (revised 2017) textbook for eighth-grade of Junior High School based on the curriculum 2013 that the Ministry of Education and culture published. This research used the content analysis method to analyse the value nationality in the textbook, and the interviews togain the English teachers perceptions on the value nationality values and how it applies to “When English Rings a Bell” (revised 2017) textbook to strengthen the result of research. The finding show that the most dominant percentage of value nationality values based on the seven indicators are related to being love of Indonesia which found (43%), followed by the willingness to sacrifice after the country (27%), pride of the motley culture (11%), receive the complex (7%), proud of being Indonesian (5%), prioritizing public interest (5%). In contrast, the least percentage was the values of heroes (0%). Those values depicted in “When English Rings a Bell” textbook aresocioculturally ingrained in Indonesian culture and appropriate to be implemented for eighth-grade Junior High School students in the teaching-learning process because it has value nationality values in each chapter which correlate to the curriculum 2013.